The Effect of Moderate Intensity Fun Aerobic Gym on HDL-C and LDL- C on Overweight Women - Saputro, Zanuar Bagus; Wardani, Tjitra; Rejeki, Purwo Sri (Folia Medica Indonesiana, 2019)
Overweight and obesity is a major health problem in throughout the world. Hyperlipidemia and obesity are risk factor the occurrence of cardiovascular disease. Exercise is recommended as a therapeutic lifestyle changes because it leads to a variety of health benefits. Fun Aerobic gymnastics aerobics one which is quite popular in the community and a gym. Describe the gymnastics fun aerobic workout's effectiveness against related to prevention of cardiovascular disease with seeing the results before and after doing gymnastics with the result of increasing levels of HDL-c and LDL/HDL Ratios as well as lowering LDL-c levels. Using design research one group pretest and posttest design with the subject as many as 19 people and given gymnastics moderate fun aerobic intensity for 45 minutes 3 day a week for 6 weeks. Gymnastics moderate fun aerobic intensity can increase HDL-c and LDL/HDL ratio and LDL-c. The paired t test results HDL-c pre test and post test (p = 0.000), LDL-c pre test and post test (p = 0,015), HDL/LDL Ratio (p = 0.000). Mean there are meaningful difference between the before and after of gymnastics. The effect of moderate intensity fun aerobic gym on the increase of HDL-c and LDL/HDL Ratio and a decrease in LDL-c in overweight women.